Peran Zakat dalam Pengentasan Kemiskinan : Perspektif Hukum Ekonomi Islam - Utami, Barti; Sunarko, Adang; Wati, Ida (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2024)
Poverty is one of the socio-economic issues that continues to be a concern in various countries, including Indonesia. Solutions to address poverty have been tried many times, but the results are still unsatisfactory. This research aims to examine the role of zakat in poverty alleviation from the perspective of Islamic economic law. Through an analysis of the relevant literature, the findings indicate that zakat has significant potential in alleviating poverty. (Zakat, 2020) Zakat is not only capable of meeting the basic needs of individuals and families in need, but it can also serve as a solution for distributing wealth more fairly and evenly. The optimization of zakat potential can be achieved through strengthening the institutions managing zakat, enhancing accountability, transparency, and the effectiveness of zakat fund distribution. This research aims to analyze the role of zakat in poverty alleviation from the perspective of Islamic economic law. This study employs a qualitative method with a literature review approach from reliable sources. Research results show that zakat has great potential in reducing poverty and improving community welfare. However, to maximize the potential of zakat, strengthening the institutions managing zakat, enhancing accountability, transparency, and the effectiveness of zakat fund distribution is needed (Anis et al., 2022). Moreover, to optimize the role of zakat, efforts are required to improve the professionalism of zakat collectors, integrate zakat distribution with economic empowerment programs, and ensure supportive regulations and government policies.